Pharmacognostical and Phytochemical Evaluation of Grewia asiatica Linn Tiliaceae Fruit Pulp and Seed - Preeti, Pandya (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmacognostical and Phytochemical Evaluation of Grewia asiatica Linn Tiliaceae Fruit Pulp and Seed